Pengaruh Progressive Muscle Relaxation (PMR) dalam Menurunkan Skala Nyeri pada Pasien Kanker Paru yang Mendapatkan Pengobatan Kemoterapi - Defi Eka Kartika; Yessy Susanty Sabri; Reni Prima Gusty (STIKes Hang Tuah Pekanbaru, 2022)
Progressive Muscle Relaxation (PMR) is a technique that focuses on maintaining a state of muscle relaxation, involving contraction and relaxation of various muscle groups from the head to the lower extremities. This study aimed to examine the effectiveness of PMR in reducing pain in lung cancer patients receiving chemotherapy. The research design used is quantitative research with a quasi-experiment approach with control group pre-test-post-test design with purposive sampling technique so that the number of respondents as many as 34 people (17 people control group and 17 people intervention group). The pain scale data collection technique uses a numeric rating scale. the results of the study found that there was a difference in the scale of pain before and after the administration of PMR in cancer patients in the intervention group with p = 0,000 (p<0.05). it is hoped that health services, especially nurses, can make PMR as an independent intervention and one of the establishments of telenursing programs in terms of monitoring pain scales in lung cancer patient receiving chemotherapy treatment.